The effects of green tea on cognitive impairments in the rat model of Alzheimer's disease: protection against inflammatory and oxidative damage. (2nd December 2022) - Amirpour, Mahsa; Mirshekar, Mohammad Ali; Sedaghat, Gohar; Montazerifar, Farzaneh; Shourestani, Shadi; Arabmoazzen, Saiedeh; Naghizadeh, Mehrdad
ABSTRACT: Introduction: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by a decrement in the number of synapses, an increment in the production of oxygen free radicals and inflammatory cytokines. Green tea (GT) plays a defensive performance in different neurodegenerative conditions, such as cognition deficit. This study investigated the neuroprotective effect of green tea (GT) on cognitive disorder, inflammation, and oxidative stress in the streptozotocin (STZ)- induced AD model. Materials and Methods: The rats were divided into four groups: (1) Control, (2) GT, (3) Alz, and (4) GT + Alz. AD was induced by the injection of STZ (3 mg/kg, bilaterally, ICV). Morris water maze and passive avoidance tests were done to evaluate the memory and learning of rats. Biochemical parameters were measured with specialized ELISA kits. Results: Briefly, data analysis revealed that GT administration for 21 days improved memory impairment induced by the injection of STZ. Pretreatment with GT enhanced time spent in the goal quarter and reduced latency time and path length. Furthermore, pretreatment with GT prevented the increment of malondialdehyde (MDA) concentration in STZ-treated rats. As a pro-inflammatory cytokine, tumor necrosis factor- α (TNF-α) concentration was suppressed with the GT pretreatment. Total antioxidant capacity was increased after GT administration in rats treated compared with AD rats. Conclusions: GT pretreatment attenuated STZ-induced learning and memory impairment through the suppression of TNF-α and MDA concentrations. The beneficial effects of GT on memory could be attributed to its protective effects on oxidative defenses.